MODEL SISTEM INFORMASI PENJAMINAN MUTU BERBASIS INTERGRASI AKREDITASI BAN-PT DAN ISO 9001:2008 DENGAN PENDEKATAN METODE EKD-CM - Mercurius Broto Legowo; Budi Indiarto; Deden Prayitno (PROSIDING SNAST, 2018)
The purpose of this research is to develop a model of quality assurance information system based on integration of BAN-PT accreditation and ISO 9001: 2008 for ISO certified university, using the approach of "Knowledge Development-Change Management (EKD-CM) method. The EKD-CM method is the result of a study conducted by Nurcan and Barios (2003) is a method in developing information system model based on the business goal model, business process model up to model information system. The use of this method will improve the knowledge of academic resources on the quality of the study program, provide reasons for alternative solutions from different perspectives, and develop knowledge in support of organizational learning. This study is the next stage of previous research showing a framework of accreditation results of BANT-PT and ISO 9001: 2008. This National Strategy Research for Institutions is a type of applied research that uses a qualitative approach.. The result of this research is a model of Quality Assurance Information System (QAIS) based on integration of BAN-PT and ISO 0001: 2008 for ISO certified higher education. By using EKD-CM method approach, this modeling will present business purpose model, business process model, and information system modeling (process modeling, data modeling, Information System architecture modeling and system application modeling). This QAIS modeling will later facilitate in software development at next stage of research in the future. This information system model will be able to support the change of study program management to improve the accreditation standard of study program significantly.